THE INFLUENCE OF CONSUMER BEHAVIOR AND PURCHASE INTEREST ON SALES VOLUME AT THE PARKIR FASHION CLOTHING STORE - Yanto Putra Firman Jaya Hulu; Ahmad Yudhira; Mella Yunita; Khamo Waruwu (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2026)
This research is motivated by the increasingly tight competition conditions in the clothing retail business and the low sales volume at the Fashion Parking Clothing Store, which is thought to be influenced by consumer behavior and purchasing interests that tend to change, the jump between product expectations and reality, and suboptimal marketing strategies. The purpose of this study was to determine the Influence of Consumer Behavior and Purchase Intention on Sales Volume at the Parkir Fashion Clothing Store. This research was conducted at the Parkir Fashion Clothing Store located at Jalan Kapten Muslim, Helvetia Tengah, Helvetia District, Medan City, North Sumatra 20117-Indonesia. The population in this study was all consumers who made purchases at the Parkir Fashion clothing store. The sampling method used in this study was a nonprobability sampling technique, resulting in a sample of 96 respondents. This study used primary data collected using a questionnaire. Data analysis methods used data analysis, multiple linear regression, classical assumptions, hypothesis testing, and coefficient of determination tests using SPSS 24 for Windows. The results showed that consumer behavior and purchasing interest partially influenced sales volume at the Parkir Fashion clothing store. Consumer behavior and purchasing interest simultaneously influenced sales volume at the Parkir Fashion clothing store. The coefficient of determination test showed that 54.6% of sales volume factors could be explained by consumer behavior and purchasing interest variables, while the remaining 43.6% was explained by other factors not examined in this study.